Impact of Epsom Salt Concentrations on the Growth and Develop-ment of Gladiolus Cultivars - Shah, Syed Saadullah; Ahmad, Masood; Ali, Hamza; Zaman, Shahid; Malik, Saima Naz; Asghar, Ali; Ullah, Ikram (BioScientific Review, 2026)
Background. Gladiolus is an important ornamental plant known for its vibrant colors and high demand in the market. Its growth is greatly affected by several factors, among which the most prominent are magnesium and sulfur deficiency. Epsom salt is a rich source of magnesium and sulfur and has the ability to improve the vegetative and reproductive attributes of different gladiolus cultivars. However, its optimum concentrations for improved growth and development need to be identified. Materials and Methods. This study was conducted at the ornamental nursery, The University of Agriculture, Peshawar, Pakistan, following a randomized complete block design with two factors. Factor A comprised Epsom salt concentrations at 0%, 2%, 4%, and 6%. While, Factor B included gladiolus cultivars, namely White Prosperity, Rosa Supreme, Nova Lux, and Advanced Red. Foliar application of Epsom salt was done when the plants reached three to five true leaf stages. Results. Among all the concentrations, Epsom salt showed greater chlorophyll content at the rate of 4%, as well as the number of florets, floret diameter, floret fresh weight, floret dry weight, spike length, and vase life. Likewise, the highest number of leaves, leaf area, floret diameter, number of florets, floret fresh and dry weight, as well as vase life, weight, and diameter of daughter cormels were observed in the Advance Red cultivar of gladiolus. Interactive effects revealed that Advance Red, with 4% Epsom salt, achieved maximum floret weight, dry matter, and vase life, while the longest spikes were recorded in White Prosperity. Conclusion. This study identifies 4% Epsom salt as the optimal concentration for enhancing gladiolus growth and floral quality, with Advanced Red emerging as the most responsive cultivar.